Inseguridad alimentaria de los hogares colombianos según localización geográfica y algunas condiciones sociodemográficas (2008)
ABSTRACT: household food security is a country s` indicator of quality of life and poverty. The characterization of these indicators is necessary to develop social policies. Objective: to describe the level of food security in Colombian families according to their geographic location and socioeconomic conditions. Materials and methods: the Household Food Security Scale was applied to 17.740 Colombian families. The prevalence of food insecurity was established in relation to their geographic place, Health security classification (Sisben), access to number of utilities, number of individuals living in a house and the average household size. Odds ratio (OR) was used to calculated food insecurity related to socioeconomic variables. Results: the prevalence of severe food insecurity was three times higher in rural areas than in urban local households. The highest prevalence was identified in the Atlantic region. The prevalence of food insecurity decreased in the same way as the health security classification (Sisben) changed, and the number of utilities and the number of rooms for house increased. However, the opposite situation was evidenced along with the average household size. Conclusion: deprive and inequity conditions influencing household food insecurity significantly, especially in these families that present moderate and severe food insecurity levels. Recommendations: to impact family’s life conditions is necessary to take actions concerning to reduce poverty, hunger and malnutrition among these people at high risk.